PENGARUH INDEKS PEMBANGUNAN MANUSIA DAN KEPADATAN PENDUDUK TERHADAP INDEKS KUALITAS LINGKUNGAN HIDUP DI PULAU JAWA TAHUN 2012-2021 - RIZKA ELFINA AULIA; AGUNG SETIA BUDI; AMIN PUJIATI (GANEC SWARA, 2024)
The decline in environmental quality will be influenced by non-human influences and human influences. Increasing environmental aspects is inversely proportional to improving economic aspects. This research uses fixed model analysis techniques to see how human development and population density have an impact on the quality of the environment on the island of Java from 2012-2021. Calculations in this research state that the human development index has a significantly positive impact on environmental quality, while population density itself has a positive and insignificant impact on the environmental quality index.